2020
DOI: 10.1021/acs.inorgchem.0c01076
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of Fluorinated Triaryl Aluminum Complexes

Abstract: The addition of the Grignard 3,4,5-Ar F MgBr to aluminum(III) chloride in ether generates the novel triarylalane Al(3,4,5-Ar F ) 3 ·OEt 2 . Attempts to synthesize this alane via transmetalation from the parent borane with trimethylaluminum gave a dimeric structure with bridging methyl groups, a product of partial transmetalation. On the other hand, the novel alane Al(2,3,4-Ar F ) 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…In addition, S. Nembenna et al [30] demonstrated compound 17 catalyzed hydroboration of aldehydes and ketones. Moreover, R. L. Melen et al [31] also found that compound 20 is an effective catalyst for the reaction of carbonyl compounds with HBpin (Scheme 1).…”
Section: Hydroboration Of Aldehydes and Ketonesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, S. Nembenna et al [30] demonstrated compound 17 catalyzed hydroboration of aldehydes and ketones. Moreover, R. L. Melen et al [31] also found that compound 20 is an effective catalyst for the reaction of carbonyl compounds with HBpin (Scheme 1).…”
Section: Hydroboration Of Aldehydes and Ketonesmentioning
confidence: 99%
“…Scheme 11. Aluminum catalyst(31) for hydroboration of alkynes. Reprinted with permission from Ref [46],.…”
mentioning
confidence: 99%
“…Quantitative substrate conversions with excellent chemoselectivities (>98%) were achieved with these particular imines, while, at the same time, generating the fastest reaction rates among the examined substrates, despite the transformations performing at −78 °C (for the selectivity purposes). Lastly, according to the results summarized in Table 1 , it appeared that this reduction protocol favored, in terms of reaction rates, ketimines over aldimines, which is not typically observed in the literature [ 10 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. At the moment, the precise reason(s) for this observation is(are) not known but it may suggest that the electrophilic step i.e., coordination of imine to BH 3 (see below) was rate determining, as one would expect that the hydride transfer (i.e., the nucleophilic step) would be less favored for ketimines over aldimines.…”
Section: Resultsmentioning
confidence: 73%
“…[63][64][65][66][67][68][69][70][71] Working on the hydroboration and hydrosilylation of various unsaturated compounds and especially on the reactivity of conjugated 1,3-diynes in these processes, we have found that literature information is often scattered, with no detailed procedures or much discussion on the process optimisation or methodology. [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87] Therefore, we have decided to build a comprehensive and critical compendium focused on this subject, which will systemise the existing knowledge on the hydroelementation of diynes in relation to the formation of different products. We will also show the possible applications of the obtained products in the synthesis of fine chemicals and materials.…”
Section: Introductionmentioning
confidence: 99%